The Effect of Teaching Style and Teacher’s Creativity to the Student’s Achievement at Christian Vocational High School of Tagari Rantepao - Panggua, Marni Sanda; Sunaryo, Tarsicius; Kailola, Lisa G. (CV. Creative Tugu Pena, 2021)
The article was to analyze the effect of teaching style and teacher’s creativity for improving the student’s achievement at Christian Vocational School of Tagari Rantepao. This research was quantitative with an expost facto research. The sample was 94 teachers at Christian Vocational High School of Tagari Rantepao. Data obtained through research instruments by questionnaires which given directly. An analyzing data was correlation and multiple linear regression analysis with SPSS application version 25. The result showed that, teaching style has significant effect on student’s achievement at Christian Vocational School of Tagari Rantepao. It can be seen from the result of data analysis where the tvalue 4,699 > ttable 2,000. The significant effect of teaching style on student’s achievement as 68,1%. Moreover, multiple linear regression analysis showed that teacher’s creativity also has significant effect on student’s achievement at Christian Vocational School of Tagari. It can be proved from the result of data analysis where the tvalue 3,051 > ttable 2,000. The significant effect of teacher’s creativity on student’s achievement as 37,2%. Teaching style (X1) and teacher’s creativity (X2) can explain student’s achievement. The result of data analysis also showed that Fcount 41,34 > Ftable 3,15. The determination coefficient as 0,579 means 57,9% the effect of teaching style and teacher’s creativity on student’s achievement at Christian Vocational School of Tagari Rantepao. Keywords: Learning Style, Teacher Creativity, Teaching Style